극저온 연료탱크용 고망간강과 스테인리스강 316L 이종금속 용접부의 가스텅스텐아크 용접재료별 기계적 성질 및 미세조직 - 조철호; Chulho Cho; 남성길; Seongkil Nam; 유성훈; Sunghoon Yu; 최명환; Myeonghwan Choi; 강남현; Namhyun Kang (대한금속·재료학회지, 60(9), 2022)
The gas tungsten arc (GTA) weldability of high-Mn (HMn) steel and austenitic stainless steel (STS) 316L using dissimilar metal welds (DMWs) was investigated, to fabricate a fuel tank for an LNG-fueled ship. Three types of welding fillers, HMn steel, STS 309LMo and Inconel 625, were applied to the DMWs. The weldability of the DMWs was examined by investigating mechanical properties at 25 and -196℃, followed by microstructural evolution and weld deformation. The GTA welding process was performed with a heat input range of 0.72-1.89 kJ/mm. All of the fillers employed in the study produced reasonable mechanical properties and low levels of precipitation, such as M 7 C 3 and Fe 3 C. However, the DN specimen using the Inconel 625 filler exhibited reduced ductility in the bending test. This was attributed to Nb-carbide precipitations at dendrite boundaries at the root weld. The DM specimen using HMn filler experienced severe thermal deformation because it had a relatively higher coefficient of thermal expansion than the other fillers during heating by arc and solidification. Therefore, STS 309LMo and HMn wires were determined to be the appropriate fillers for the DMW of HMn steel and STS 316L for cryogenic applications, and the HMn wire requires attention to weld deformation. (Received 18 April, 2022; Accepted 21 June, 2022)